The Effectiveness Of The Let’s Exercise Fundamental Movement Skills Model On Children With Mild Intellectual Disabilitys In Special Need Education Of Palembang - Selvi Atesya Atesya Kesumawati; Husni Fahritsani; Novri Asri; Endang Pratiwi (UNIB Press, 2020)
This study aims to produce and test the effectiveness of the fundamental movement skills (FMS) learning model product, let's exercise on students with mild intellectual disability (ID) in primary special need education (SDLB) Palembang City. This research took place in 2018 before the pandemic Covid-19 era. The subjects of the small group trial were 10 students and 4 teachers, and the subjects for the large group trial were 23 students and 4 teachers for grade 1 in 3rd SDLB serving children with ID in Palembang City. The data analysis technique used the z test effectiveness test (parameter) and the Wilcoxon test (non parameter). The results showed that the large group trial data for aspects of basic movement skills, cognitive abilities, pleasure (fun), and focus of attention obtained an average value of trial 2 greater than trial 1, as well as the z-count value of the lets exercise model of play activity is greater. from the z-table value (1.96), so the difference is significant. So it can be concluded that the game model lets exercise be effective for improving FMS, cognitive abilities, pleasure, and focus on attention of grade 1 students with mild ID in SDLB.